Identifying and Prioritizing Factors Affecting Supply Chain Financing in the Energy Sector - Asadi Asadabad, Reza; Borhani, Seyed Abbas; Safa, Mojgan; Badiei, Hossein (Management Strategies and Engineering Sciences, 2024)
The energy sector, due to its complex and evolving nature, requires innovative financing methods. The aim of this study is to identify and prioritize factors influencing supply chain financing in the energy sector. This research is applied in orientation and quantitative in methodology. The theoretical population of the study consisted of experts active in the energy sector with a solid background in financing and supply chain financing. Judgment sampling was employed in this study. The methods used in this research included Fuzzy Delphi and CoCoSo. The Fuzzy Delphi method was utilized to screen the research factors, while CoCoSo was applied for final prioritization of the factors. The primary data collection tools were an expert assessment questionnaire and a prioritization questionnaire. This study was conducted in three stages. In the first step, 21 factors were identified through literature review and interviews with experts. In the next step, these factors were screened using expert assessment questionnaires and the Fuzzy Delphi method. Ten factors, which achieved a favorable defuzzified value, were selected for final prioritization. The selected factors were ranked using the CoCoSo method. The prioritized factors included: the degree of integration of information systems within supply chain components, the penetration rate of data-driven technologies in the energy supply chain, and the level of banks' control over the country’s financing sector. Practical recommendations were developed based on the key factors identified in the study. Some of these recommendations included: focusing on the compatibility and adaptability of technologies with existing systems during technology transfer, using fourth-generation technologies to integrate the supply chain, and enhancing the diversity of financing methods in the country through the development of fintechs and financial startups.